Antimicrobial Resistance Profiles and Tetracycline Resistance Genes of Escherichia coli in Mediterranean Mussel and Sea Snails Collected from Black Sea, Turkey - TERZİ, Ertuğrul (Alinteri Zirai Bilimler Dergisi, 2018)
Aquatic environments are often affected by and exposed to anthropogenic pollutants including antimicrobials used as disease prevention and feed additives. Antimicrobial resistance is a major problem both in animal and in human health worldwide. In this study, Mediterranean mussel (Mytilus galloprovincialis) and Sea snail (Rapana venosa) samples were collected seasonally from the coastline of Black Sea. A total of 54 Escherichia coli were isolated from Mediterranean mussel and Sea snail collected from the coast of Artvin, Rize, Trabzon and Giresun, Turkey. Antimicrobial resistance and the presence of tetracycline (tet) resistance genes (tetA, tetB, tetC, tetD, and tetE) in E. coli isolates were investigated. Antimicrobial susceptibility test determined that 83.3 % of the isolates exhibited resistance to sulfamethoxazole. Resistance to ampicillin and aztreonam was as 66.7 % and 37.0 % among the tested antimicrobials, respectively. The lowest resistant antimicrobial was florfenicol (1.9 %). tetC resistance gene was detected in more than 50% of the isolates. Among the tet resistance genes, tetC was found in the most common gene followed by tetB, tetA, tetE, and tetD. At least one tet gene was detected in 88% of the isolates, and 46% of the isolates had two or more tet genes. The presence of tet resistance genes in E. coli in aquatic environments indicates that these isolates may be a reservoir of tet resistance genes. They may also exhibit an important role in the spread of genes among the pathogenic and non-pathogenic bacteria.
Keywords: Antimicrobial; Mytilus galloprovincialis; Rapana venosa; Tetracycline resistance gene; Antimikrobiyal; Mytilus galloprovincialis; Rapana venosa; Tetrasiklin direnç geni; 3. Good health